Site specificity as the decolonial model : an interpretive study of the Groote Schuur Menagerie - Moon, Shannon (School of Architecture, Planning and Geomatics, 2017)
The Groote Schuur Menagerie, commonly known as the 'Rhodes' Zoo', is located next to the University of Cape Town on the foothills of Table Mountain. A deserted display of historical relics, this site can be seen as a tangible and perceived symbol of colonisation. Despite not being a focus of the #RhodesMustFall movement to date, the Groote Schuur menagerie was also established by Cecil John Rhodes' and was part of his imperial agenda. Abandonment, physical change over time and immersion of the zoo structures in spontaneous vegetation growth, has blurred the distinction between the architectural objects and the original topography, creating a new hybrid landscape with a particular microclimate and ambiance. This study presents the argument that theories on Site Specificity, as a model of site interrogation and design, is the most appropriate to the discourse of decolonization as it is inherently a de-colonized method of reading the site. Through conducting a site specific analysis on the Groote Schuur Menagerie site, in addition to consulting archived material. I will argue that the current site conditions are a manifestation of the colonial and decolonial, suggestion that the landscape is essential 'new' in its current condition, and therefore appropriate for new identity.